Sexual Dysfunction and Spermogram Analysis in Men - Abdurahmanov Kamoliddin Dustqobilovich.; Abdiev Ilhom Allayorovich; Boboyorov Sardor Uchqun o’g’li (Zien Journals, 2021)
Sexual conflict has been going on since the dawn of humanity. In many cases, a defect in one sex leads to the deterioration of these conditions and the state of extinction. This article discusses sexual dysfunction, which is now very common in men, and therefore the analysis and treatment of spermograms in this disease.
Keywords: male reproductive system; sexually active; ejaculation; Sperm concentration